A Review on Structural Configurations of Magnetorheological Fluid Based Devices Reported in 2018–2020 - Hua, Dezheng; Liu, Xinhua; Li, Zengqiang; Fracz, Pawel; Hnydiuk-Stefan, Anna; Li, Zhixiong (Frontiers in Materials, 2021)
Magnetorheological fluid (MRF) is a kind of smart materials with rheological behavior change by means of external magnetic field application, which has been widely adopted in many complex systems of different technical fields. In this work, the state-of-the-art MRF based devices are reviewed according to structural configurations reported from 2018 to 2020. Based on the rheological characteristic, the MRF has a variety of operational modes, such as flow mode, shear mode, squeeze mode and pinch mode, and has unique advantages in some special practical applications. With reference to these operational modes, improved engineering mechanical devices with MRF are summarized, including brakes, clutches, dampers, and mounts proposed over these 3 years. Furthermore, some new medical devices using the MRF are also investigated, such as surgical assistive devices and artificial limbs. In particular, some outstanding advances on the structural innovations and application superiority of these devices are introduced in detail. Finally, an overview of the significant issues that occur in the MRF based devices is reported, and the developing trends for the devices using the MRF are discussed.